Postural Adjustments Following ACL Rupture and Reconstruction: A Longitudinal Study - Labanca, Luciana; Laudani, Luca; Mariani, Pier Paolo; Macaluso, Andrea (International Journal of Sports Medicine, 2018)
Longitudinal changes in compensatory and anticipatory postural adjustments around the knee were investigated from rupture of ACL until return to play after reconstruction. Twelve ACL-injured participants (ACL-P) were asked to respond to unpredictable and predictable perturbations before (T1), 2 (T2) and 6 months after (T3) reconstruction. Twelve healthy participants served as controls. Compensatory and anticipatory latencies of vastus lateralis (VL) and medialis (VM) were measured with respect to the arrival of perturbations. ACL-P showed delayed compensatory latencies compared to controls at T1 for VL (101±32 ms vs 63±7 ms) and VM (117±36 ms vs 75±17 ms) and at T2 for VL (94±20 ms vs 63±7 ms) and VM (94±27 ms vs 71±11 ms). ACL-P showed earlier anticipatory latencies than controls for VL at T1 (-69±44 ms vs -12±12 ms) and T2 (-46±17 ms vs -16±12 ms). At T3, ACL-P showed delayed compensatory latencies for VL (91±18 ms vs 56±21 ms) and VM (95±13 ms vs 66±4 ms), whilst anticipatory latencies were restored. Rehabilitation should address delayed compensatory responses.
Keywords: knee Surgery; postural control; functional assessment; rehabilitation